2015
DOI: 10.1080/1059924x.2014.976732
|View full text |Cite
|
Sign up to set email alerts
|

Job Characteristics and Work Safety Climate Among North Carolina Farmworkers With H-2A Visas

Abstract: Migrant farmworkers are a vulnerable population. Migrant farmworkers with H-2A visas are the only agricultural workers with temporary work permits. Little research has directly focused on the job characteristics and work safety of workers with H-2A visas. This analysis (1) describes their personal and job characteristics, job hazards, and stressors; (2) describes their perceived work safety climate; and (3) examines associations of perceived work safety climate with job characteristics, job hazards, and stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
1
17
0
1
Order By: Relevance
“…Almost all of the participants had H-2A visas. These visas provide farmworkers with some protections, but at the same time they may experience intimidation from their employers (Bauer, 2007; Arcury et al, 2015). Although most of these farmworkers are married or living as married, none would be living with their wives and families as they could not afford to bring them to the US, and their employers would not provide room and board for them while living in the farmworker camps.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the participants had H-2A visas. These visas provide farmworkers with some protections, but at the same time they may experience intimidation from their employers (Bauer, 2007; Arcury et al, 2015). Although most of these farmworkers are married or living as married, none would be living with their wives and families as they could not afford to bring them to the US, and their employers would not provide room and board for them while living in the farmworker camps.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the farmworkers who participated in this study had H-2A visas; while these temporary work visas may result in worker intimidation, 62 as well as separation from family and community, they do afford these workers with some sense of protection. 63 …”
Section: Discussionmentioning
confidence: 99%
“…Although requirements are in place to provide farmworkers with H-2A visas with health insurance, Workers Compensation, and transportation for health care, these requirements are often not met and farmworkers are often reluctant to ask for these benefits for fear of offending their employers. 13,14 Finally, many Latino farmworkers have health beliefs that differ from those of conventional medicine, 5,15,16 so may turn to available traditional healers to address their injuries and illness. The use of traditional healers may influence how and when farmworkers use conventional health care; the use of traditional healers is an indicator of their access to conventional medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Skaer and colleagues 17 found that 21% of Mexican American women in Washington State acknowledged having received treatment from ā€œ curanderos , sobadores , or spiritualistsā€ in the past 5 years; use of these traditional healers was related to fewer years living in the United States, a preference for speaking Spanish over English, and having received medical care in Mexico in the previous 5 years. Andrews and colleagues 14 interviewed Latino mothers in Washington State concerning child health and found about a third used sobadores , 8% curanderos , and none used herbalists or spiritualists. Chavez 15 surveyed Mexican immigrants to San Diego, California, and found that very few had used curanderos (1.3%), spiritualists (0.4%), witches (0.1%), or sobadores (5.7%) in the past.…”
Section: Introductionmentioning
confidence: 99%